P–581 The day of blastocyst biopsy and the chromosomal constitution. Evaluation of 5125 embryos by Next Generation Sequency (NGS). (6th August 2021) - Villanuev. Zúñiga, P E; Huayhua, J; Noriega-Hoces, L; Llerena, G; Noriega-Portella, J; Noriega-Portella, L; Guzman, L
Abstract: Study question: Is there a relationship between the day of blastocyst biopsy and the results NGS analysis? Summary answer: Embryos biopsied on day 6 or 7 are associated with the increased probability of being an aneuploidy embryo and less likely to be mosaic embryo. What is known already: There is controversy about whether an embryo that reaches the blastocyst stage on day 5 has a higher chance of being euploid than embryos which are biopsied later. In our study, chromosome constitution was evaluated by next-generation sequencing (NGS)-based preimplantation genetic testing for aneuploidy (PGT-A) and confounding factors were eliminated. Study design, size, duration: Data was collected retrospectively from June 2016 to January 2020 Participants/materials, setting, methods: In total, 5125 blastocyst (day 5=2914, day 6 N = 2154 and day7 N = 57), generated from 1318 cycles were analysed with PGT-A. The chromosome constitution for each embryo was classified as euploid, aneuploid and mosaic. A multilevel model was made and associations betwwen variables by logistic regression were adjusted according to maternal age, SART blastocyst grade, fertilization method, biopsy operator and blastocyst stage. Main results and the role of chance: The mean maternal age was 36.2 ± 4.2. Euploid rate was 62.1% and 37.9% (day 5 and day 6–7 respectively), aneuploidy rate was 47.0% and 53.0% (day 5 and day 6–7, respectively), mosaicism rate was 59.6% and 40.4% (day 5 and day 6–7, respectively) (p < 0.001). Embryos biopsied on day 6–7 have a significantly lower probability to be euploid and mosaicism than embryos biopsied on day 5 ((OR = 0.76 [0.68–0.86]); (OR = 0.84 (0.73 – 0.96) respectively) (p < 0.001). On the contrary, embryos biopsy on day 5 were significantly more likely to be euploid than day 6–7 (OR = 1.63[1.42–1.86]) (p < 0.001). Limitations, reasons for caution: The results observed in this study should be confirmed using a larger number of samples. For the NGS analysis, a chromosome with a variation between 20 to 80% was considered mosaic. Wider implications of the findings: The present study revealed that embryos that reach blastocyst classified as full to hatched on day 5 are more like to be euploid compared to slow growing embryos. Trial registration number: non-clinical trials